Biobehavioral Mechanisms Associated With Nonhealing Wounds and Psychoneurologic Symptoms (Pain, Cognitive Dysfunction, Fatigue, Depression, and Anxiety) in Older Individuals With Chronic Venous Leg Ulcers. Issue 4 (July 2019) - Stechmiller, Joyce K.; Lyon, Debra; Schultz, Gregory; Gibson, Daniel J.; Weaver, Michael T.; Wilkie, Diana; Ferrell, Anastasiya V.; Whitney, Joanne; Kim, Junglyun; Millan, Susan B.
The prevalence and incidence of chronic venous leg ulcers (CVLUs) are increasing worldwide, as are the associated financial costs. Although it has long been known that their underlying etiology is venous insufficiency, the molecular aspects of healing versus nonhealing, as well as the psychoneurologic symptoms (PNS; pain, cognitive dysfunction, fatigue, depression, and anxiety) associated with CVLUs remain understudied. In this biobehaviorally focused review, we aim to elucidate the complex mechanisms that link the biological and molecular aspects of CLVUs with their PNS. Innovations in "omics" research have increased our understanding of important wound microenvironmental factors (e.g., inflammation, microbial pathogenic biofilm, epigenetic processes) that may adversely alter the wound bed's molecular milieu so that microbes evade immune detection. Although these molecular factors are not singularly responsible for wound healing, they are major components of wound development, nonhealing, and PNS that, until now, have not been amenable to systematic study, especially over time. Further, this review explores our current understanding of the molecular mechanisms by which the immune activation that contributes to the development and persistence of CVLUs also leads to the development, persistence, and severity of wound-related PNS. We also make recommendations for future research that will expand the field of biobehavioral wound science. Biobehavioral research that focuses on the interrelated mechanisms of PNS will lead to symptom-management interventions that improve quality of life for the population burdened by CVLUs.